Determination of Realistic Mathematics Education on Problem Solving with Numeracy Literacy Covariables - Ni Nyoman Lisna Handayani (Universitas Pendidikan Ganesha, 2023)
The ability to solve problems in everyday life is the main competency that must be possessed by students in the 21st century. Realistic mathematics education is able to bridge the abstract concepts of mathematics obtained in class with the real world. This study aims to analyze the effect of realistic mathematics education on problem solving with numeracy literacy covariables in fourth grade students at elementary school level. This research is an experimental research with The Posttest-Only Control-Group Design. A total of 50 students were selected as research subjects. Numerical literacy data was collected using a numeracy literacy test and problem solving data using multiple choice tests. Data were analyzed using covariate analysis. The results showed that there was an effect of realistic mathematics education on problem solving of 18.235, after the controlled literacy covariable was 30.464 and the contribution of numeracy literacy to problem solving was 59.4%. The results of this study have implications for the implementation of the independent curriculum in improving students' problem-solving skills and numeracy literacy.